Silicon drift detector monolithic arrays for X-ray spectroscopy - Agostini, G.; Ambrosino, F.; Antonelli, M.; Aquilanti, G.; Bellutti, P.; Bertuccio, G.; Borghi, G.; Bosisio, L.; Campana, R.; Cautero, G.; Ceraudo, F.; Cirrincione, D.; et al. (Frontiers in Detector Science and Technology, 2025)
The efficient detection of low-energy X-rays at the keV level with the best possible energy resolution requires the application of silicon drift detectors (SDDs) and advanced application specific integrated circuits (ASICs). Their widespread use in material sciences, alongside dedicated basic science projects, has long been restricted to single, selected SDD elements working at low temperatures. This is because of the limits incurring in the quite elaborated planar technology production process and the need to reach very low leakage current levels, together with the need for highly specialized readout electronics. We describe, in this review work, the concrete outcomes of the efforts of the ReDSoX collaboration to develop high energy resolution detection systems working at near room temperature based on multi-pixel monolithic silicon drift detectors and custom-designed advanced readout electronics capable of dealing with high photon fluxes, developed for specific projects but suitable for a variety of applications.